WORLDVIEW-PHILOSOPHIC PARADIGM AS GENDER RELATIONS CONTEXT - Bilosorochka, Svitlana (Theory and Practice of Public Administration, 2019)
Problem statement. In regard to practical implementation, the provisions of the Constitution and laws of Ukraine, aimed to ensure parity gender relations in Ukraine, are interpreted through the lens of the socially established archetypes, stereotypes, traditions, values, priorities which are demarked by socio-philosophic paradigms determining the further development of relations between the man and the woman. The paper objective is studying of the socio-philosophical paradigms as the context for the gender relations in public administration. The tasks of the paper are as follows: – to characterize the main socio-philosophic paradigms; – to determine the need for and expediency of replacing the socio-political paradigms with a process of achieving parity gender relations in public administration. Recent research and publications analysis. Interpreting the gender relations in public administration through the lens of worldview-philosophic theories and concepts have been researched and introduced into the scientific discourse by V. Коrzhenko, І. Lazor, V. Sychova and others. The diverse types and standards of the scientific rationale, which coexist and replace one another in science, were studied by Kuhn; however, there is still a necessity for researching the gender relations in public administration with regard to socio-philosophic paradigms as their context. Presentation of the basic material of the research. A further development of gender relations is determined by the social norms. The context is constantly being constructed and modified through beliefs, traditions, archetypes, attitudes, and values. The worldview-philosophic paradigm at the present stage of gender relations research gives rise to discussions, without providing grounds for laying an emphasis on the gender of God or shifting the focus onto the meaning of the ideal of Virgin as a representation of loving-kindness and protection; or using the anthropocentric principle within the scope of the universal human principles of co-existence and social justice. Conclusions from the research and prospects for further scientific surveys. In summation of the above, we may state that the existence of the discourse testifies to a change of the socio-philosophical paradigm, which calls for consideration of the content of social norms, and respect for the principle of anthropocentrism and social equity.